2020
DOI: 10.1039/c9tc06918f
|View full text |Cite
|
Sign up to set email alerts
|

Super-coercive electric field hysteresis in ferroelectric plastic crystal tetramethylammonium bromotrichloroferrate(iii)

Abstract: Ionic plastic crystals are part of an emerging class of hybrid organic–inorganic ferroelectrics. Their super-coercive electric field hysteresis bares the signatures of ferroelectric switching, including interesting contributions from defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
4
4
0
Order By: Relevance
“…Indeed, in agreement with our computational predictions as well as Ref. [31] no hysteresis loops were observed for this field. The finding provides experimental support for our computational prediction of a large intrinsic coercive field.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Indeed, in agreement with our computational predictions as well as Ref. [31] no hysteresis loops were observed for this field. The finding provides experimental support for our computational prediction of a large intrinsic coercive field.…”
supporting
confidence: 93%
“…Second, if the applied field is lower than the coercive field for a given temperature the ferroelectric loops cannot occur (or will be highly distorted). Indeed it was observed experimentally, that below 40 kV=cm no hysteresis loops occur [31]. We can also see that increase in frequencies causes an increase in the coercive field, that is supercoercivity, reported experimentally [31].…”
supporting
confidence: 71%
See 2 more Smart Citations
“…[8][9][10][11] Early studies have shown that molecular ferroelectrics are uniaxial, [12][13][14][15][16][17][18][19] so that their ferroelectric functionality was restricted in a single-crystal form because the polarization could only be switched along the single polarization axis. With the development of targeted design strategies, [20][21][22][23] multiaxial ferroelectricity was further discovered in molecular systems, such as hybrid perovskites, [24][25][26] simple salts, [27][28][29][30][31][32] and plastic crystals, [33][34][35] in which several ferroelectric axes allow for arbitrarily directed polarization to orient along the electric field, hence rendering ferroelectric properties in a polycrystalline form. Moreover, due to several advantages such as light weight, mechanical flexibility, low acoustical impedance, and easy processability, the multiaxial molecular ferroelectrics are expected to replace the widely used inorganic oxides in the next-generation flexible electronics.…”
Section: Introductionmentioning
confidence: 99%